Surface finish based analysis of turned titanium alloys workpieces. (18th October 2010) - Huerta, M.; Sanchez Carrilero, M.; Alvarez, M.; Salguero, J.; Marcos, M.; Arroyo, P.
Titanium alloy-based airship parts must be machined under high surface finish requirements. Previous works have shown the relationship between the surface roughness and the tool changes in the first instants of turning processes. From these results, new tests have been performed in an aeronautical factory, showing that surface quality is strongly influenced by the tool surface changes in form of built-up edge (BUE) and built-up layer (BUL). SEM/EDS analysis has shown that these effects take place sequentially. BUL is quickly formed as stratified TiOx films, changing the tool surface. This allows developing BUE. Evolution of both effects provokes an Ra reduction with the length of machining. On the other hand, feed, f, is the most influent cutting parameter in the Ra value. Furthermore, a quasi-linear model Ra(f) has been found for describing the relationship between roughness and feed.